Modeling the impact of land use/land cover change on soil erosion: in Suluh River Basin, Northern Ethiopia - Hailay Hagos Entahabu; Amare Sewnet Minale; Emiru Birhane (Journal of Degraded and Mining Lands Management, 2023)
The Suluh river basin is subjected to soil erosion due to land use and land cover change. Yet, the impact of land use/land cover change soil erosion has not been applied in the study area. Thus, the current study focused on the modeling of the impact of land use/land cover changes on soil erosion in the Suluh river basin, the northern highland part of Ethiopia. Landsat image data sources were used to achieve the objectives. Ancillary data was also used. The nearest neighbor's fuzzy way of classification and the land change modeler for modeling, and the revised universal soil loss equation model for estimating the soil erosion rate were employed. Both qualitative and quantitative data were analyzed qualitatively and quantitatively. The study's findings confirmed that cultivated land, bare land, and built-up areas significantly increased while areas occupied by natural vegetation such as forest land, shrub lands, and grazing lands decreased at a rapid rate in between 1990 to 2018. The predicted results suggest the continuation of the trend up to 2048 if business as usual is continued. The annual mean of soil lost in the study area was about 36.31, 43.32, and 47.78 in the years 1990, 2002, 2018, and will be 56.54, and 71.62 tons per hectare per year in 2028, and 2048, respectively. When we consider 15 t ha−1 year−1 as the maximum tolerable soil loss (TSL) rate for ease of presentation, the areas above the TSL have increased from 88.3% in 1990 to 88.6% in 2002 and to 89.6% in 2018, and are expected to increase to 89.9% and 99.8% in 2028 and 2048 periods, respectively. Thus, land use and land cover change information and its impact on soil erosion should be taken under consideration by land use planners to apply sustainable land management activities in the Suluh river basin.